Navigasi Realtime Menggunakan Incremental GPS Path Logging Algorithm dan Visualisasi Interaktif Berbasis Web: Pengembangan Sistem Pelacakan Posisi dan Arah Pengguna Berbasis Browser dengan Mapbox GL JS dan Kompas Digital - Taufiqurrahman Taufiqurrahman; Septian Enggar Simatupang; Rizki Ramadhansyah; Indah Clara Sari; Ihsan Rafli (Jurnal Minfo Polgan, 2025)
The advancement of web technologies and mobile device sensors has opened new opportunities in the development of lightweight and flexible realtime navigation systems. This study aims to develop a web-based navigation system utilizing the Incremental GPS Path Logging Algorithm for step-by-step route logging, and integrating a digital compass to align the map view with the device’s orientation. The map visualization is implemented using Mapbox GL JS, enabling a third-person interactive display in realtime. Built with JavaScript and React JS, the system was tested in lightweight mobility scenarios such as walking and cycling. Results showed the system accurately tracked user positions, efficiently updated routes without full redraw, and displayed speed, distance, and duration in realtime. The use of DeviceOrientationEvent provided a more intuitive navigation experience, despite challenges like sensor lag or permission restrictions on certain devices. This system demonstrates great potential for personal tracking and lightweight mobility use cases across platforms without app installation. Future research may focus on 3D visualization optimization, integration of historical data, and advanced route analytics